Lactobacillus plantarum PADA FESES INDIVIDU DEWASA SEHAT YANG MENGONSUMSI Lactobacillus plantarum IS-10506 DARI DADIH [Lactobacillus plantarum in Stool of Apparently Healthy Adults Consuming Lactobacillus plantarum IS-10506 from Dadih] - Azmier Adib; Mardiastuti H Wahid; Pratiwi Sudarmono; Ingrid S. Surono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2013)
A placebo double blind pre-post human study was conducted in apparently healthy adults. There were two treatment groups consisting of Group A and B representing probiotic and placebo group, respectively. Twenty four participants were randomly assigned, each supplemented with either placebo or probiotic Lactobacillus plantarum IS-10506. The micro encapsulated powder was given at a dose of 2.6x1010 CFU/day for 21 consecutive days. Stool samples were collected before and after the supplementation. The fresh stool samples were analyzed for the viability of Lactobacillus sp. by conventional plate count method in MRS agar. Some stool samples were kept frozen to be analyzed by using real time PCR to trace back the availability of Lactobacillus plantarum with species specific primer. The Lactobacillus sp. in stools of healthy adults given microencapsulated probiotic Lactobacillus plantarum IS-10506 powder was significantly more than those who consumed microencapsulated placebo powder. Molecular detection by qPCR confirmed the availability of Lactobacillus plantarum in fecal samples of the probiotic group after given the supplementation for 21 days. The molecular detection validation confirmed that probiotic Lactobacillus plantarum was available in the fecal samples of the probiotic group of healthy adults. However, the availability and viability of Lactobacillus plantarum were not consistently found in the intestinal tract.